The mulberry bush : a novel - McCarry, Charles (Mysterious Press, 2015)
Falling in love with a famous Argentinean revolutionary's daughter who he hopes will further his ambition to exact revenge against the handlers who ended his father's career years earlier, a maverick spy is caught in a web of deceit with ties to the Cold War.